Stereoselective synthesis of beta-C-Allyl- and beta-C-propargyl-D-arabinofuranosides - Ramana, C. V.; Narute, Sachin B.; Gonnade, Rajesh G.; Patil, Rahul S. (Synthesis-Stuttgart, 2008)
The stereoselective synthesis of beta-configured C-allyl- and C-propargyl-D-arabinofuranosides (4,7-anhydro-1,2,3-deoxy-D-gluco-oct-1-enitols and -oct-1-ynitols) was addressed by employing allylation/propargylation of a dialdofuranose under aqueous Barbier reaction conditions and acid-catalyzed furan ring transposition of 5-O-mesyl-manno-oct-7-eno- or 5-O-mesyl-manno-oct-7-ynofuranoside derivatives.
Keywords: Allylation; Barbier reaction; C-glycoside; D-mannose; propargylation; Ring transposition

Synthesis of C(27)–C(38) fragment of aflastatin A - Narute, Sachin B.; Ramana, C.V. (Tetrahedron, 2013)
Efforts at finding out a strategy for the synthesis of the densely hydroxylated C(27)–C(48) fragment of aflastatin A have been described. The initial studies dealing with alkyne–epoxide coupling using a linear polyol epoxide resulted in a debenzylative cycloetherification leading to a C-arabinoside derivative. This problem has been addressed by applying an epoxide pendant on a furanosyl unit. With the model alkyne, the epoxide–alkyne coupling proceeded smoothly. Subsequently, following a sequence of [Pd]-mediated alkynone cycloisomerization/stereoselective hydroboration–oxidation, the synthesis of the central C(27)–C(38) fragment has been executed. When employed, the original C(33)–C(48) alkyne, the coupling and the cycloisomerizations are facile. However, the resulting glycals are unstable, thus warranting a revision in our approach.
Keywords: Aflastatin; Epoxide–alkyne coupling; ω-Alkynone cycloisomerization; Palladium catalysis; Hydroboration

Synthesis of C-disaccharides through a one-pot alkynol cycloisomerization-reductive deoxygenation - Narute, Sachin B.; Rout, Jeetendra Kumar; Ramana, Chepuri V. (Chemistry-A European Journal, 2013)
Keywords: C-disaccharides; carbohydrates; Epoxide-alkyne coupling; Gold catalysis; Reductive deoxygenation